THE ROLE OF SOCIAL MEDIA IN EMPOWERING RURAL ECONOMIES: A CASE STUDY OF KENYA - Dlela, Martin (Komitmen: Jurnal Ilmiah Manajemen, 2024)
This study explores the role of social media in empowering rural economies, focusing on a case study in Kenya. In recent years, social media platforms have emerged as significant tools for economic development, especially in developing countries. This research investigates how rural communities in Kenya leverage social media to enhance economic activities, promote local products, and access market information. Using a mixed-method approach, the study combines qualitative interviews with quantitative surveys to analyze the impact of social media on economic empowerment. The findings reveal that social media facilitates market access, enhances networking opportunities, and provides a platform for knowledge sharing among rural entrepreneurs. However, challenges such as digital literacy, internet accessibility, and cultural barriers hinder the full potential of social media utilization in these areas. The study contributes to the understanding of digital tools in rural economic development and provides insights for policymakers and practitioners to optimize social media strategies for community empowerment.